PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY. TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Maheswari, Ni Putu Dewi Utami; Damayanthi, I Gst Ayu Eka (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
The objective of this research is to examine and to obtain empirical evidence regarding the direct and indirect effect of corporate social responsibility disclosure on corporate value with profitability as the intervening variable. This research was conducted on energy sector corporate listed on the Indonesia Stock Exchange for the 2019-2021 period. The number of samples was 72 in 3 years of observation, with the method of collecting samples using with purposive sampling technique. The data analysis technique used path analysis and sobel test. The results of the analysis show that CSR disclosure has a positive and significant effect on profitability, CSR disclosure and profitability has a positive and significant effect on corporate value, and the result of sobel test stated that profitability can partial mediate the effect of CSR disclosure on corporate value. Future researchers are expected to be able to increase the period of years in the research, for example 5-10 years, in order to provide a more diverse variety of research, and it is recommended to try to increase the number of samples, namely all companies listed on the Indonesian Stock Exchange and add at least one new variable that can influence company value which has not been used in this research.